Ecological stone slab and preparation method thereof
By using double-bonded modified polyurethane resin and epoxy oligomers in ecological stone slabs to form a crosslinked network structure, the problem of insufficient impact resistance of existing stone slabs is solved, and the mechanical properties and aesthetics are improved.
Patent Information
- Application Number
- CN202411140406.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-20
AI Technical Summary
During the production, transportation and use of existing ecological stone slabs, they are prone to cracks, deformation and damage caused by external forces, and have low impact resistance, which affects aesthetics and usage performance.
Using double bond modified polyurethane resin and epoxy oligomer as binders, the mechanical strength and impact resistance of stone slabs are enhanced through the network structure of physical interpenetration and chemical cross-linking, and combined with the photothermal double curing method to buffer the curing stress .
It significantly improves the mechanical properties and impact resistance of ecological stone slabs, reduces the generation of cracks, and improves the yield and aesthetics of appearance texture.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stone slabs, in particular to an ecological stone slab and a preparation method thereof. Background Art
[0002] Eco-stone slabs are made of natural stone fragments as the main body, resin and other materials as binders, and are pressed. Compared with traditional natural stone slabs, eco-stone slabs are light in texture, smooth in surface and beautiful in appearance. They are commonly used decorative slabs in the construction and home furnishing industries and are deeply favored by consumers.
[0003] The existing ecological stone slabs inevitably need to use adhesives during the preparation process. Compared with unsaturated resin adhesives, epoxy resins have obvious advantages in mechanical properties and bonding effects, and are therefore widely used. However, since the molecular structure of epoxy resins contains rigid benzene rings, the resins are brittle but have poor toughness after curing, resulting in low impact resistance of the stone slabs. During production, transportation, and use, they are easily cracked by external forces, resulting in deformation and breakage of the stone slabs, affecting the appearance and performance of the stone slabs and causing unnecessary losses. Summary of the invention
[0004] The purpose of the present invention is to provide an ecological stone slab and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an ecological stone slab and a preparation method thereof, comprising the following steps:
[0006] Step 1:
[0007] S11: Disperse triphenylmethane triisocyanate and polymerization inhibitor in acetone, add hydroxyethyl acrylate at 40-45°C and nitrogen environment, and control the addition time to be 30-45 minutes; use dibutyltin dilaurate as a catalyst, heat to 55-60°C for reaction for 0.5-1 hour, and continue to heat to 70-80°C for reaction for 3-4 hours to obtain double-bond modified diisocyanate;
[0008] S12: Mixing double-bond modified diisocyanate and isophorone diisocyanate to obtain an isocyanate mixture; in a nitrogen environment, mixing polyethylene glycol 2000 and 1,4-butanediol, heating to 60-70° C., adding the isocyanate mixture, stirring and reacting for 0.5-1 h, adding dibutyltin dilaurate and acetone, reacting for 4-6 h, and then adding ethylenediamine for end-capping, reacting for 0.5-1.5 h to obtain a double-bond modified polyurethane resin;
[0009] Step 2:
[0010] S21: Mix 2,2'-diallyl bisphenol A and epichlorohydrin, add benzyl triethylammonium chloride, heat to 100-105°C in a nitrogen environment, react for 3-4 hours, cool and add NaOH solution, react for 18-20 hours, extract with ethyl acetate, wash with deionized water, evaporate excess solvent, and vacuum dry to obtain epoxy monomer;
[0011] S22: Disperse 2,2'-diallyl bisphenol A in anhydrous toluene, heat to 75-80°C under nitrogen protection, add dimethylphenylsilane, heat to 100-105°C, react with Karstedt catalyst, react for 15-18h, remove impurities by rotary evaporation, and vacuum dry to obtain organosilicon-modified bisphenol A;
[0012] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A for 3 to 4 hours at a reaction temperature of 110 to 130° C.; washing and drying to obtain epoxy oligomer;
[0013] Step 3:
[0014] S31: mixing, crushing and sieving marble, quartz, granite, pebbles and rutile to obtain stone powder;
[0015] S32: Mix double-bond modified polyurethane resin, epoxy oligomer, epoxy resin, stone powder, curing agent and initiator evenly and pour into the mold, place for 18-24 hours, vibrate and press, and solidify; open the mold, grind and polish to obtain ecological stone slabs.
[0016] Furthermore, in S11, triphenylmethane triisocyanate and hydroxyethyl acrylate are mixed at a molar ratio of isocyanate to hydroxyl of 3:1.
[0017] Furthermore, in S12, the double bond modified diisocyanate and isophorone diisocyanate are mixed in a weight ratio of 1:(10-20) to obtain an isocyanate mixture.
[0018] Furthermore, in S12, the amount of each component in the double bond modified polyurethane resin, by weight, is 60 to 70 parts of polyethylene glycol 2000, 7 to 10 parts of 1,4-butanediol, 30 to 37 parts of isocyanate mixture, 0.2 to 0.3 parts of dibutyltin dilaurate, 5 to 8 parts of acetone, and 2 to 3 parts of ethylenediamine.
[0019] Furthermore, in S21, the amount of each component in the epoxy monomer is, by weight, 12 to 14 parts of 2,2'-diallyl bisphenol A, 15 to 18 parts of epichlorohydrin, 0.2 to 0.3 parts of benzyltriethylammonium chloride, and 10 to 13 parts of NaOH solution.
[0020] Furthermore, in S22, the amounts of the components in the organosilicon-modified bisphenol A are, by weight, 8 to 8.4 parts of 2,2'-diallyl bisphenol A and 8.8 to 9.2 parts of dimethylphenyl silane.
[0021] Furthermore, in S23, the epoxy monomer and the silicone-modified bisphenol A are reacted at a molar ratio of epoxy group to phenolic hydroxyl group of (3-3.5):1.
[0022] Furthermore, in S31, the contents of the various components in the stone powder are, by weight, 50-75 parts of marble, 15-20 parts of quartz, 10-15 parts of granite, 8-13 parts of pebbles, and 5-8 parts of rutile.
[0023] Furthermore, in S32, in the ecological stone slab, the amount of each component, by weight, is 30~38 parts of double bond modified polyurethane resin, 30~41 parts of epoxy oligomer, 47~53 parts of epoxy resin, 220~260 parts of stone powder, 36~42 parts of curing agent, and 1~2 parts of initiator.
[0024] Furthermore, in S32, the vibration pressing method is: vibration pressing under an ambient pressure of 90~100 kPa, and a vibration frequency of 30~50 Hz; the curing method is UV curing for 0.5~1h, curing at 80~100°C for 1~2h, and curing at 100~120°C for 1~2h.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention crushes a variety of natural stones into stone powder, uses epoxy resin and polyurethane resin as binders, and adds epoxy oligomers with synergistic effects, which synergize with epoxy resin and polyurethane resin during the curing process to form a physically interpenetrating and chemically cross-linked network, thereby enhancing the mechanical strength and impact resistance of the ecological stone slab.
[0026] In the present invention, the polyurethane resin used is a double-bond modified polyurethane resin. The specific preparation method is: using triphenylmethane triisocyanate and hydroxyethyl acrylate as raw materials, reacting by controlling the molar ratio of isocyanate to 3:1 to obtain a double-bond modified diisocyanate; mixing the double-bond modified diisocyanate and isophorone diisocyanate, and reacting with polyethylene glycol 2000 to obtain a double-bond modified polyurethane resin.
[0027] In the present invention, the epoxy oligomer is obtained by polymerization of epoxy monomer and organosilicon-modified bisphenol A. The epoxy monomer uses 2,2'-diallyl bisphenol A as a raw material, and the epoxy group is introduced by reacting the phenolic hydroxyl group with epichlorohydrin; the organosilicon-modified bisphenol A uses 2,2'-diallyl bisphenol A as a raw material, and the organosilicon is introduced by addition reaction of double bonds with silicon hydrogen in dimethylphenylsilane. The epoxy monomer contains two epoxy groups, and the organosilicon-modified bisphenol A contains two phenolic hydroxyl groups. The epoxy group reacts with the phenolic hydroxyl group to achieve polymerization.
[0028] In the material mixing stage, polyurethane and epoxy resin are used as binders, and epoxy oligomers are added. Since epoxy resin oligomers contain silicone, the viscosity can be reduced, so that the binder and stone powder are mixed more evenly. The molecular weight of epoxy oligomers is small, and it is easier to fill in the gaps between stone powder, polyurethane resin and epoxy resin, thereby improving the density. It should be noted that the amount of epoxy monomer and silicone-modified bisphenol A has an effect on the molecular weight of the polymer. When the amount of silicone-modified bisphenol A is too high, the molecular weight of the polymer is large, and the corresponding viscosity is also greater, which is not conducive to material mixing, and the high molecular weight polymer is difficult to fill the gaps in the material; at the same time, a high content of silicone will cause defects in the cross-linking network, thereby reducing the cross-linking density and causing a decrease in the mechanical properties of the material. Therefore, the product performance is best when the molar ratio of epoxy group to phenolic hydroxyl group is controlled to (3~3.5):1.
[0029] In the curing stage, the present invention uses a light-heat dual curing method. Since the epoxy oligomer contains double bonds and epoxy groups, it can be chemically cross-linked with the double-bond modified polyurethane resin after ultraviolet irradiation; after heating, under the action of the curing agent, the epoxy oligomer can be cross-linked with the epoxy resin, so that the polyurethane resin and the epoxy resin form a network structure in two ways: physical interpenetration and chemical cross-linking, which greatly improves the cross-linking density; segmented curing buffers the adverse effects caused by the curing stress of different resins, and effectively avoids the generation of cracks during the pressing process. The ecological stone slab prepared by the present invention has a high yield rate, good mechanical properties, and beautiful appearance and texture. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The materials used in the present invention and their sources are as follows: the polymerization inhibitor is polymerization inhibitor 701, the curing agent is triethylenetetramine, the epoxy resin is epoxy resin E-51, which comes from Hebei Linyuan Fine Chemical Co., Ltd.; and the initiator is photoinitiator 1173.
[0032] Embodiment 1: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0033] Step 1:
[0034] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 40°C and in a nitrogen environment, and control the addition time to be 30 minutes; use dibutyltin dilaurate as a catalyst, heat to 55°C for reaction for 0.5 hours, and continue to heat to 70°C for reaction for 3 hours to obtain a double-bond modified diisocyanate;
[0035] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 60° C., 34 g of the isocyanate mixture was added, stirred and reacted for 0.5 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 4 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 0.5 h to obtain a double bond modified polyurethane resin;
[0036] Step 2:
[0037] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 100° C. under a nitrogen environment, reacted for 3 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 18 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0038] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 75°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 100°C, and the reaction was catalyzed by Karstedt catalyst for 15 h. Impurities were removed by rotary evaporation, and the organic silicon-modified bisphenol A was obtained by vacuum drying;
[0039] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 3 hours, and the reaction temperature is 110° C.; washing and drying to obtain epoxy oligomer;
[0040] Step 3:
[0041] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0042] S32: 36kg double bond modified polyurethane resin, 30kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 18 hours and vibrated at 90kPa ambient pressure with a vibration frequency of 30Hz. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 0.5 h, cured at 80 ° C for 1 h, and cured at 100 ° C for 1 h. The mold was opened and the material was ground and polished to obtain the ecological stone slab.
[0043] Embodiment 2: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0044] Step 1:
[0045] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 45°C and in a nitrogen environment, and control the addition time to be 35 minutes; use dibutyltin dilaurate as a catalyst, raise the temperature to 60°C for reaction for 0.5h, and continue to raise the temperature to 75°C for reaction for 3.5h to obtain a double-bond modified diisocyanate;
[0046] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 65° C., 34 g of the isocyanate mixture was added, stirred and reacted for 1 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 5 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 1 h to obtain a double bond modified polyurethane resin;
[0047] Step 2:
[0048] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 105° C. under a nitrogen environment, reacted for 3.5 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 19 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0049] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 80°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 105°C, and the reaction was catalyzed by Karstedt catalyst for 16 h. Impurities were removed by rotary evaporation, and the organic silicon-modified bisphenol A was obtained by vacuum drying;
[0050] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 3.5 hours, and the reaction temperature is 115° C.; washing and drying to obtain epoxy oligomer;
[0051] Step 3:
[0052] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0053] S32: 36kg double bond modified polyurethane resin, 30kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 20 hours and vibrated at 95kPa ambient pressure with a vibration frequency of 40Hz. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 85°C for 1.5 hours, and cured at 105°C for 1.5 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0054] Embodiment 3: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0055] Step 1:
[0056] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 45°C and in a nitrogen environment, and control the addition time to be 45 minutes; use dibutyltin dilaurate as a catalyst, raise the temperature to 60°C for reaction for 1 hour, and continue to raise the temperature to 80°C for reaction for 4 hours to obtain a double-bond modified diisocyanate;
[0057] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 70° C., 34 g of the isocyanate mixture was added, stirred and reacted for 1 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 6 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 1.5 h to obtain a double bond modified polyurethane resin;
[0058] Step 2:
[0059] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 105° C. under a nitrogen environment, reacted for 4 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 20 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0060] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 80°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 105°C, a Karstedt catalyst was used for the reaction, the reaction was carried out for 18 hours, impurities were removed by rotary evaporation, and the organosilicon-modified bisphenol A was obtained by vacuum drying;
[0061] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 4 hours, and the reaction temperature is 130° C.; washing and drying to obtain epoxy oligomer;
[0062] Step 3:
[0063] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0064] S32: 36kg double bond modified polyurethane resin, 30kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 24 hours and vibrated at 100kPa ambient pressure with a vibration frequency of 50Hz. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 90°C for 2 hours, and cured at 110°C for 2 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0065] Embodiment 4: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0066] Step 1:
[0067] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 40°C and in a nitrogen environment, and control the addition time to be 30 minutes; use dibutyltin dilaurate as a catalyst, heat to 55°C for reaction for 1 hour, and continue to heat to 80°C for reaction for 3 hours to obtain a double-bond modified diisocyanate;
[0068] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 70° C., 34 g of the isocyanate mixture was added, stirred and reacted for 1 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 4 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 0.5 h to obtain a double bond modified polyurethane resin;
[0069] Step 2:
[0070] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 100° C. under a nitrogen environment, reacted for 4 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 18 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0071] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 75°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 100°C, and the reaction was catalyzed by Karstedt catalyst for 15 h. Impurities were removed by rotary evaporation, and the organic silicon-modified bisphenol A was obtained by vacuum drying;
[0072] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 4 hours, and the reaction temperature is 110° C.; washing and drying to obtain epoxy oligomer;
[0073] Step 3:
[0074] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0075] S32: 36kg double bond modified polyurethane resin, 33kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 20 hours and vibrated at 90kPa ambient pressure with a vibration frequency of 30Hz. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 90°C for 1 hour, and cured at 100°C for 2 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0076] Embodiment 5: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0077] Step 1:
[0078] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 45°C and in a nitrogen environment, and control the addition time to be 45 minutes; use dibutyltin dilaurate as a catalyst, heat to 60°C for reaction for 1 hour, and continue to heat to 80°C for reaction for 3-4 hours to obtain a double-bond modified diisocyanate;
[0079] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 60° C., 34 g of the isocyanate mixture was added, stirred and reacted for 0.5 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 5 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 1.5 h to obtain a double bond modified polyurethane resin;
[0080] Step 2:
[0081] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 105° C. under a nitrogen environment, reacted for 3 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 20 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and the mixture was dried in vacuo to obtain an epoxy monomer;
[0082] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 80°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 100°C, and the reaction was catalyzed by Karstedt catalyst for 18 hours, impurities were removed by rotary evaporation, and the organic silicon modified bisphenol A was obtained by vacuum drying;
[0083] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 3 hours, and the reaction temperature is 115° C.; washing and drying to obtain epoxy oligomer;
[0084] Step 3:
[0085] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0086] S32: 36kg double bond modified polyurethane resin, 37kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 24 hours and vibrated at a frequency of 50Hz under an ambient pressure of 100kPa. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 90°C for 2 hours, and cured at 110°C for 2 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0087] Embodiment 6: An ecological stone slab and a preparation method thereof, comprising the following steps:
[0088] Step 1:
[0089] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 40°C and in a nitrogen environment, and control the addition time to be 45 minutes; use dibutyltin dilaurate as a catalyst, heat to 60°C for reaction for 1 hour, and continue to heat to 80°C for reaction for 4 hours to obtain a double-bond modified diisocyanate;
[0090] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 70° C., 34 g of the isocyanate mixture was added, stirred and reacted for 1 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 6 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 1.5 h to obtain a double bond modified polyurethane resin;
[0091] Step 2:
[0092] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 105° C. under a nitrogen environment, reacted for 4 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 20 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0093] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 80°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 105°C, a Karstedt catalyst was used for the reaction, the reaction was carried out for 18 hours, impurities were removed by rotary evaporation, and the organosilicon-modified bisphenol A was obtained by vacuum drying;
[0094] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A at a molar ratio of epoxy group to phenolic hydroxyl group of 3:1, the reaction time is 4 hours, and the reaction temperature is 120° C.; washing and drying to obtain epoxy oligomer;
[0095] Step 3:
[0096] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0097] S32: 36kg double bond modified polyurethane resin, 41kg epoxy oligomer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 24 hours and vibrated at 95kPa ambient pressure with a vibration frequency of 45Hz. The mixture was vibrated at a wavelength of 365nm and an intensity of 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 90°C for 2 hours, and cured at 110°C for 1.5 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0098] Comparative Example 1: The polyurethane resin and the epoxy resin were directly blended, and the other parameters were the same as those in Example 1.
[0099] Step 1:
[0100] Under nitrogen environment, 65g of polyethylene glycol 2000 and 8g of 1,4-butanediol were mixed and heated to 60°C, 34g of isophorone diisocyanate was added, stirred and reacted for 0.5h, 0.2g of dibutyltin dilaurate and 8g of acetone were added, reacted for 4h, and 3g of ethylenediamine was added for end-capping, and reacted for 0.5h to obtain a polyurethane resin;
[0101] Step 2:
[0102] S21: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0103] S22: Mix 36kg of polyurethane resin, 49kg of epoxy resin, 260kg of stone powder, 38kg of curing agent and 1.5kg of initiator evenly, pour into the mold, place for 18 hours, vibrate and press at an ambient pressure of 90kPa with a vibration frequency of 30Hz; cure at 80℃ for 1h and at 100℃ for 1h, open the mold, grind and polish to obtain an ecological stone slab.
[0104] Comparative Example 2: The content of organosilicon-modified bisphenol A in the epoxy oligomer was increased, and the other parameters were the same as those in Example 2.
[0105] Step 1:
[0106] S11: Disperse triphenylmethane triisocyanate and a polymerization inhibitor in acetone, add hydroxyethyl acrylate at a molar ratio of isocyanate group to hydroxyl group of 3:1 at 45°C and in a nitrogen environment, and control the addition time to be 35 minutes; use dibutyltin dilaurate as a catalyst, raise the temperature to 60°C for reaction for 0.5h, and continue to raise the temperature to 75°C for reaction for 3.5h to obtain a double-bond modified diisocyanate;
[0107] S12: double bond modified diisocyanate and isophorone diisocyanate were mixed in a weight ratio of 1:10 to obtain an isocyanate mixture; under a nitrogen environment, 65 g of polyethylene glycol 2000 and 8 g of 1,4-butanediol were mixed and heated to 65° C., 34 g of the isocyanate mixture was added, stirred and reacted for 1 h, 0.2 g of dibutyltin dilaurate and 8 g of acetone were added, reacted for 5 h, and 3 g of ethylenediamine was added for end-capping, and reacted for 1 h to obtain a double bond modified polyurethane resin;
[0108] Step 2:
[0109] S21: 14 g of 2,2'-diallyl bisphenol A and 17 g of epichlorohydrin were mixed, 0.3 g of benzyltriethylammonium chloride was added, and the mixture was heated to 105° C. under a nitrogen environment, reacted for 3.5 h, cooled to 60° C., 13 g of 30 wt.% NaOH solution was added, and the mixture was reacted for 19 h. The mixture was extracted with ethyl acetate, washed with deionized water, excess solvent was evaporated, and vacuum dried to obtain an epoxy monomer;
[0110] S22: 8.4 g of 2,2'-diallyl bisphenol A was dispersed in anhydrous toluene, the temperature was raised to 80°C under nitrogen protection, 9.2 g of dimethylphenylsilane was added, the temperature was raised to 105°C, and the reaction was catalyzed by Karstedt catalyst for 16 h. Impurities were removed by rotary evaporation, and the organic silicon-modified bisphenol A was obtained by vacuum drying;
[0111] S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A in a molar ratio of epoxy group to phenolic hydroxyl group of 1:1, the reaction time is 3.5 hours, and the reaction temperature is 115° C.; washing and drying to obtain an epoxy polymer;
[0112] Step 3:
[0113] S31: 75 kg of marble, 15 kg of quartz, 13 kg of granite, 11 kg of pebbles, and 7 kg of rutile are mixed, crushed, and sieved to obtain stone powder;
[0114] S32: 36kg double bond modified polyurethane resin, 30kg epoxy polymer, 49kg epoxy resin, 260kg stone powder, 38kg curing agent and 1.5kg initiator were mixed evenly and poured into the mold. The mixture was placed for 20 hours and vibrated at 95kPa ambient pressure with a vibration frequency of 40Hz. The wavelength was 365nm and the intensity was 150μW / cm 2 The material was cured under UV light for 1 hour, cured at 85°C for 1.5 hours, and cured at 105°C for 1.5 hours. The mold was opened, and the material was ground and polished to obtain an ecological stone slab.
[0115] Experiment: The ecological stone slabs in Examples 1 to 6 and Comparative Examples 1 to 2 were sampled, the sample size was 150 mm × 100 mm × 12 mm, and the performance of the samples was tested using a strength testing machine at a rate of 1 mm / min; the impact test was performed on the sample with a notch depth of 2 mm using a steel ball weighing 50 kg. The experimental results are shown in the following table:
[0116]
[0117] Conclusion: The data of Examples 1 to 6 show that the ecological stone slab prepared by the present invention has excellent mechanical properties, good tensile strength and impact toughness. The data of Example 1 and Comparative Example 1 show that compared with the scheme of the present invention, the polyurethane resin and the epoxy resin are blended, and the two are cross-linked only by physical interpenetration after curing, so the tensile strength and impact toughness of the stone slab are not as good as those of Example 1; the data of Example 2 and Comparative Example 2 show that the strength of the stone slab decreases when the content of organosilicon-modified bisphenol A in the epoxy oligomer is increased.
[0118] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an ecological stone slab, characterized in that: The following steps are involved: Step 1: S11: Disperse triphenylmethane triisocyanate and polymerization inhibitor in acetone, add hydroxyethyl acrylate at 40-45°C and nitrogen environment, and control the addition time to be 30-45 minutes; use dibutyltin dilaurate as a catalyst, heat to 55-60°C for reaction for 0.5-1 hour, and continue to heat to 70-80°C for reaction for 3-4 hours to obtain double-bond modified diisocyanate; S12: Mixing double-bond modified diisocyanate and isophorone diisocyanate to obtain an isocyanate mixture; in a nitrogen environment, mixing polyethylene glycol 2000 and 1,4-butanediol, heating to 60-70° C., adding the isocyanate mixture, stirring and reacting for 0.5-1 h, adding dibutyltin dilaurate and acetone, reacting for 4-6 h, and then adding ethylenediamine for end-capping, reacting for 0.5-1.5 h to obtain a double-bond modified polyurethane resin; Step 2: S21: Mix 2,2'-diallyl bisphenol A and epichlorohydrin, add benzyl triethylammonium chloride, heat to 100-105°C in a nitrogen environment, react for 3-4 hours, cool and add NaOH solution, react for 18-20 hours, extract with ethyl acetate, wash with deionized water, evaporate excess solvent, and vacuum dry to obtain epoxy monomer; S22: Disperse 2,2'-diallyl bisphenol A in anhydrous toluene, heat to 75-80°C under nitrogen protection, add dimethylphenylsilane, heat to 100-105°C, react with Karstedt catalyst, react for 15-18h, remove impurities by rotary evaporation, and vacuum dry to obtain organosilicon-modified bisphenol A; S23: using butyl triphenylphosphine bromide as a catalyst, reacting epoxy monomer and organosilicon-modified bisphenol A for 3 to 4 hours at a reaction temperature of 110 to 130° C.; washing and drying to obtain epoxy oligomer; Step 3: S31: mixing, crushing and sieving marble, quartz, granite, pebbles and rutile to obtain stone powder; S32: Mix double-bond modified polyurethane resin, epoxy oligomer, epoxy resin, stone powder, curing agent and initiator evenly and pour into the mold, place for 18-24 hours, vibrate and press, and solidify; open the mold, grind and polish to obtain ecological stone slabs.
2. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S11, triphenylmethane triisocyanate and hydroxyethyl acrylate are mixed at a molar ratio of isocyanate to hydroxyl of 3:
1.
3. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S12, the amount of each component in the double-bond modified polyurethane resin, by weight, is 60-70 parts of polyethylene glycol 2000, 7-10 parts of 1,4-butanediol, 30-37 parts of isocyanate mixture, 0.2-0.3 parts of dibutyltin dilaurate, 5-8 parts of acetone, and 2-3 parts of ethylenediamine; wherein, in the isocyanate mixture, the weight ratio of the double-bond modified diisocyanate to isophorone diisocyanate is 1:(10-20).
4. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S21, in the epoxy monomer, the amounts of the components used, by weight, are 12 to 14 parts of 2,2'-diallyl bisphenol A, 15 to 18 parts of epichlorohydrin, 0.2 to 0.3 parts of benzyltriethylammonium chloride, and 10 to 13 parts of NaOH solution.
5. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S22, the amount of each component in the organosilicon-modified bisphenol A is, by weight, 8 to 8.4 parts of 2,2'-diallyl bisphenol A and 8.8 to 9.2 parts of dimethylphenyl silane.
6. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S23, the epoxy monomer and the silicone-modified bisphenol A are reacted at a molar ratio of epoxy group to phenolic hydroxyl group (3-3.5):
1.
7. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S31, the content of each component in the stone powder, by weight, is 50-75 parts of marble, 15-20 parts of quartz stone, 10-15 parts of granite, 8-13 parts of pebbles, and 5-8 parts of rutile.
8. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S32, the amount of each component in the ecological stone slab, by weight, is 30~38 parts of double bond modified polyurethane resin, 30~41 parts of epoxy oligomer, 47~53 parts of epoxy resin, 220~260 parts of stone powder, 36~42 parts of curing agent, and 1~2 parts of initiator.
9. The method for preparing an ecological stone slab according to claim 1, characterized in that: In S32, the vibration pressing method is: vibration pressing under an ambient pressure of 90~100kPa, and a vibration frequency of 30~50Hz; the curing method is UV curing for 0.5~1h, curing at 80~100℃ for 1~2h, and curing at 100~120℃ for 1~2h.
10. The ecological stone slab prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Composite artificial stone plate and preparation method thereof
CN104163017A
Preparation method for novel quartz stone plate
CN104926198A
High strength artificial quartz stone sheet and preparation method thereof
CN105819748A
Environment-friendly reinforced and strengthened type modified epoxy resin grouting and preparation method thereof
CN106800903A
High-strength eco-stone slab and preparation method thereof
CN115925321A
